Implantable Cardioverter Defibrillator System with Floating Atrial Sensing Dipole: A Single‐Center Experience. Issue 10 (9th May 2014) - IORI, MATTEO; GIACOPELLI, DANIELE; QUARTIERI, FABIO; BOTTONI, NICOLA; MANARI, ANTONIO
<x xml:space="preserve">Abstract</x> Background The concept of a single‐lead dual‐chamber implantable cardioverter defibrillator (ICD) with floating sensing atrial dipole has been proven safe and functional. We report a single‐center experience with this ICD system; the major focus of the work is on the recorded atrial activation and its stability on a medium term follow‐up. Methods Thirteen patients received a DX ICD (BIOTRONIK SE & Co, Berlin, Germany) with the Linox Smart S DXProMRI ICD lead; the implantation data were reported. Daily P‐ and R‐wave sensing amplitude was collected and followed up during 200 days; their coefficient of variance (CV) was calculated. In addition, all the atrial and ventricular high‐rate episodes were analyzed. Results The total x‐ray exposure time was 3.9 ± 1.8 minutes. The overall mean sensing was 4.2 ± 1.9 mV for P wave and 12.9 ± 4.5 mV for R wave. The CV was significantly higher for the P‐wave amplitude than for the R‐wave one (0.25 ± 0.11 vs 0.08 ± 0.06; P < 0.001). A total of 27 high ventricular rate episodes were recorded and correctly discriminated by the device. Fifty‐six high atrial rate episodes were recorded, 49 were true arrhythmic events. Conclusions The single‐lead ICD system with floating atrial dipole provides reliable atrial sensing amplitude over time. The physician, without the implantation of an additional lead, has the atrial information that may be used for the discrimination of supraventricular tachyarrhythmia/ventricular tachycardia, for the early detection of atrial fibrillation episodes and for the evaluation of changes in the patient's heart status.